MISYAR MARRIAGE: ITS LEGAL STATUS AND OVERSIGHT - Seerwan Azeez Shakor; Daban Salam Omar Abbas (International Journal of Business, Law and Political Science, 2026)
Objective: The research aims to compile various scholarly opinions, outline the relevant Sharia evidence, and determine the ruling on this form of marriage. It also examines the origins of Misyar marriage, the specific rights a woman may waive, and the legal perspective regarding the practice. To define the concept of misyar marriage in linguistic and technical terms and to determine its legal nature. To clarify the reasons behind the spread of misyar marriage in contemporary societies. To outline the essential elements of misyar marriage and the conditions for its validity from both religious and legal perspectives. To analyse the legal status of misyar marriage and the extent to which it is recognised in personal status laws. To highlight the role of legal and judicial oversight in protecting the rights arising from misyar marriage. Method: Descriptive, analytical, and historical methodologies were employed, as they are best suited to the nature of the study. The historical approach was used to trace the origins of this issue and the reasons that led to its emergence in the lives and circumstances of Muslims. The inductive approach was employed to compile the relevant Islamic texts, opinions and fatwas concerning the issue. The analytical approach was applied to conduct an analytical study of these fatwas, texts and legal opinions with a view to arriving at a legal ruling, giving preference to one opinion over another, or formulating a new opinion on the matter. Results: It has been found that misyar marriage gives rise to jurisprudential and legal controversy due to the conflict between the validity of its Islamic legal elements and its contravention of certain objectives of marriage based on family stability. The research revealed a lack of clear legislative regulation of misyar marriage in many personal status laws, leading to differing legal positions regarding it. Weak oversight of misyar marriage makes it difficult to protect spousal rights, particularly with regard to maintenance, parentage and family safeguards. The study revealed that certain forms of misyar marriage are exploited to circumvent the legal and social obligations inherent in traditional marriage. The study demonstrated that the official registration of misyar marriages is an essential means of reducing disputes and safeguarding the legal rights of both parties and their children. Novelty: This study is part of a series of publications discussing Misyar marriage and its associated rulings, as well as the role of Islamic jurisprudence in addressing contemporary developments and emerging issues. The research combines Islamic jurisprudential opinions, Sharia evidence, and personal status law to examine the legal status of Misyar marriage together with the role of legal and judicial oversight in protecting the rights arising from it.